2018
DOI: 10.35188/unu-wider/2018/469-8
|View full text |Cite
|
Sign up to set email alerts
|

Campaign externalities, programmatic spending, and voting preferences in rural Mexico: The case of Progresa-Oportunidades-Prospera programme

Abstract: This study has been prepared within the UNU-WIDER project on 'The political economy of social protection systems', which is part of a larger research project on 'The economics and politics of taxation and social protection'.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 94 publications
0
7
0
Order By: Relevance
“…While weak institutionalization in the provision of social transfers can indeed facilitate clientelistic forms of pro-poor redistribution and offer a double-dividend to political elites because of the reasons discussed in Section , we cannot entirely rule out the possibility of opportunistic regimes in more competitive democratic systems enjoying an incumbency advantage via tactical redistribution, as has been reported from Latin America (De La O 2013;Filipovich et al 2018;Lazar 2004;Luccisano and Macdonald 2012) and Asia (Curato 2017;Hadiz 2016;Jaffrelot and Tillin 2017;Thompson 2016;Wyatt 2013), where large social trans-…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…While weak institutionalization in the provision of social transfers can indeed facilitate clientelistic forms of pro-poor redistribution and offer a double-dividend to political elites because of the reasons discussed in Section , we cannot entirely rule out the possibility of opportunistic regimes in more competitive democratic systems enjoying an incumbency advantage via tactical redistribution, as has been reported from Latin America (De La O 2013;Filipovich et al 2018;Lazar 2004;Luccisano and Macdonald 2012) and Asia (Curato 2017;Hadiz 2016;Jaffrelot and Tillin 2017;Thompson 2016;Wyatt 2013), where large social trans-…”
Section: Resultsmentioning
confidence: 86%
“…The literature of clientelism has long emphasized the strong association between clientelistic regimes and poverty (Bardhan et al 2010;Díaz-Cayeros and Magaloni 2009;Remmer 2007;Wantchekon 2003). In the particular case of social transfer schemes, a scarce literature highlights the presence of strategic choices that help incumbents maximize the electoral returns on transfer programmes, even under programmatic principles (Filipovich et al 2018).…”
Section: Poverty Targetingmentioning
confidence: 99%
“…The evidence shows mixed effects. Filipovich et al (2018) found no pro-incumbent effect of the Mexican CCT (Progresa-Oportunidades-Prospera) program on the 2000 and 2012 presidential elections, but registered a significant and negative effect in the 2006 election. There is also evidence that politicians benefit in local elections from the implementation of cash transfers programs (Rodríguez-Chamussy, 2015; Linos, 2013).…”
Section: Section 1: Money and Political Supportmentioning
confidence: 82%
“…More competitive political systems have also meant that political incentives for the opportunistic incumbent to manipulate spending on social assistance have been salient across the Global South (Block ). Thus, rigorous targeting mechanisms have been increasingly adopted to constrain political clientelism, although with limited success (Filipovich, Niño‐Zarazúa, and Santillán‐Hernández ; Rawlings and Rubio ; Sewall ).…”
Section: Welfare and Redistribution In Social Assistancementioning
confidence: 99%